Kalibrasi Arah Kiblat Masjid Agung Parepare Prespektif Fiqih dan Ilmu Falak - ABD. Karim Faiz (Universitas Wahid Hasyim Semarang, 2022)
Syekh Ali As-Shobuni in his Tafsir Ayatul Ahkam explained that according to Imam As-Syafi'i, the obligation to face the Qibla is an absolute obligation to face the 'ainul ka’bah (building of the Kaaba) both for those who are inside the Grand Mosque or outside the Grand Mosque . As for those who are outside the Grand Mosque and cannot see the Kaaba directly, they must study knowledge that can accurately and accurately give directions facing the Qibla, namely Astrology. The existence of Astrology and the spread of Astrology is the reason why calibration of the Qibla direction of mosques is mandatory, so is the Great Mosque of A.G.K.H. Abdul Rahman Ambo Dalle, Parepare City. The initial conclusions of the researchers were based on Google Earth-based measurements of the Qibla direction of the Great Mosque of A.G.K.H. Abdul Rahman Ambo Dalle, Parepare City deviated to the south. The purpose of this study is to describe the use of the Qibla direction method at the Great Mosque of A.G. KH. Abdul Rahman Ambo Dalle, Parepare and analyzed history and calibrated Qibla direction with contemporary reckoning using the Google Earth application tools, istiwa sticks and theodolite. The results showed that the method of measuring the Qibla direction of the Great Mosque of Parepare City uses the Compass method. Qibla direction calibration based on the Google Earth method found Qibla deviation. As for the calibration results with the Stick of Istiwa' method, it was found that the Qibla direction was deviated by 5o 30'. The Qibla Direction Calibration result with the theodolite method is 6o. Based on these 3 methodologies it was concluded that the Qibla direction of the Grand Mosque of Parepare City is not accurate. Keywords: Effectiveness; Harmony; Tolerance Syekh Ali As-Shobuni dalam karyanya Tafsir Ayatul Ahkam menjelakan bahwa menurut Imam As-Syafi’i, kewajiban menghadap kiblat merupakan kewajiban muthlak manghadap ‘ainul ka’bah (bangunan ka’bah) baik bagi yang berada di dalam Masjidil Haram ataupun diluar masjidil haram. Adapun yang berada diluar Masjidil Haram dan tidak dapat melihat langsung ka’bah maka wajib mempelajari ilmu yang dapat dengan tepat dan akurat memberikan arah menghadap kiblat yakni Ilmu Falak. Eksistensi Ilmu Falak dan menyebarnya Ilmu Falak menjadi sebab kalibrasi arah kiblat masjid menjadi wajib, begitu juga Masjid Agung A.G.K.H. Abdul Rahman Ambo Dalle Kota Parepare. Kesimpulan awal peneliti berdasarkan pengukuran berbasis Google Earth arah kiblat Masjid Agung A.G.K.H. Abdul Rahman Ambo Dalle Kota Parepare melenceng ke arah selatan. Tujuan Penelitian ini yang mendeskripsikan penggunaan metode arah kiblat Masjid Agung A.G. KH. Abdul Rahman Ambo Dalle Kota Parepare dan menganalisis historis dan kalibrasi arah kiblat dengan hisab kontemporer menggunakan alat aplikasi Google Earth, tongkat istiwa’ dan theodholite. Hasil penelitian menunjukkan bahwa metode pengukuran arah kiblat Masjid Agung Kota Parepare menggunakan metode Kompas. Kalibrasi arah kiblat berdasarkan metode Google Earth ditemukan kemelencengan arah kiblat. Adapun hasil kalibrasi dengan metode Tongkat Istiwa’ ditemukan kemelencengan arah kiblat sebesar 5o 30’. Hasil Kalibrasi Arah Kiblat dengan metode theodholite ialah 6o. Berdasarkan 3 metodologi tersebut disimpulkan bahwa arah kiblat masjid agung kota parepare tidak akurat. Kata kunci: Efektifitas; Kerukunan; Toleransi